Failure analysis of adhesive surface damage in sandwich plates under compressed loads. Issue 22 (16th November 2020) - Liu, Xiaoman; Du, Guojun; Yan, Huiming; Cheng, Shuliang
Abstract: Failures of honeycomb sandwich plates are analyzed using experiments and three-dimensional (3D) finite element simulations to understand the failure mechanism. Meanwhile, correlations of the critical load and various physical parameters (e.g., height and thickness of the core) are investigated. The results demonstrated that the core height and skin thickness have significant effects on the compressed load buckling of the honeycomb sandwich plates, the core density is a sub-critical sensitive factor, while wall thickness and spacing of the cell, and the sandwich modulus have negligible effects. Cracking on the adhesive surface is the dominant factor to reduce the buckling critical load of the laminated plate, which leads to failures of sandwich plates. The ultimate failure of the sandwich panel is attributed to severe deformations that lead to local cracking of the entire cemented adhesive surface. Due to the bonding of the adhesive surface defects, the actual loads related to the core height are large enough to cause compressions with local buckling. Hence, the actual loads cannot reflect the performance of the sandwich panels. It is recommended to use panels with appropriate thicknesses below the sandwich and moderate grid density in the design.